Rethinking Communication Education: Journalism Students' Self-Efficacy and Professional Attitudes in Turkey - Sönmez, Ilkay Ceren; Borazan, Emre Alperen (IGI Global, 2025)
This research explores the relationship between journalism students' professional self-efficacy perceptions and their professional attitudes within the context of communication education in Turkey. Conducted with 401 students at Firat University, the findings reveal that demographic background, professional experiences, and educational environments significantly influence self-efficacy beliefs. Notably, students who actively participate in journalism practices exhibit higher self-efficacy and more positive professional attitudes. These results highlight the importance of practical engagement-such as hands-on journalism experience, interaction with the media sector, and access to technology-in shaping students' professional identity and motivation. The study recommends integrating experience-based learning environments into journalism curricula to enhance student engagement and career preparedness in the communication field. © 2026, IGI Global Scientific Publishing. All rights reserved.
Keywords: Computer aided instruction; Education computing; Professional aspects; Communication fields; Educational environment; Experience-based learning; Journalism students; Learning environments; Professional experiences; Professional identity; Self efficacy; Self-efficacy beliefs; Student engagement; Students